STRATEGI BERTAHAN HIDUP NELAYAN PADA SAAT MUSIM PENGHUJAN DI KAMPUNG NELAYAN KELURAHAN OESAPA KECAMATAN KELAPA LIMA KOTA KUPANG - Bullu, Novita; Samin, Mikael; Hasan, Muhammad Husain (Jurnal Geografi, 2023)
The aim of this research is to find out the strategies used by people in fishing villages to meet the needs of their families. This research uses a qualitative approach with data collection methods using observation, interviews and documentation. The conclusion of this research is: the condition of the community in Fisherman's Village can be said to live in ease, as evidenced by the community's dependence on marine products to meet their family's needs. To meet their family's needs, they go to sea to fish using tools such as motorized boats and nets used to catch fish. The strategy that people usually use as an alternative job when the weather does not allow them to go to sea or when the rainy season arrives is by looking for side jobs that people do, such as trading, being a motorbike taxi driver, being a construction worker and so on. These alternative jobs are carried out by the community to survive and meet the needs of their families during the rainy season. It is hoped that this strategy can help fishermen meet the needs of their families.